2020
DOI: 10.1121/10.0001915
|View full text |Cite|
|
Sign up to set email alerts
|

Recognizing individual concert halls is difficult when listening to the acoustics with different musical passages

Abstract: This article presents a listening experiment in which the listeners' task was to recognize the acoustics of a seat in a specific concert hall. Stimuli included two short passages extracted from a Beethoven symphony and samples of a solo violin auralized to four real concert halls. In each trial, listeners were presented with a reference and four alternatives with one correct match. In the "same" condition, the reference and the alternatives contained the same source sound. In the "different" condition, the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Interestingly, perceptual and cognitive ability estimates derived from the two listening tests show very low and insignificant correlations among each other. This finding indicates that the two test paradigms indeed require fundamentally different abilities, confirming the previous findings suggesting that acoustical listening expertise is not a single skill but consists of several abilities (Kuusinen and Lokki, 2020). however, expertise in the perceptual assessment of room acoustic conditions can only be achieved by familiarization and specific training of all participants prior to the listening test, whereas self-reports and socio-demographic information represent rather unreliable indicators.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, perceptual and cognitive ability estimates derived from the two listening tests show very low and insignificant correlations among each other. This finding indicates that the two test paradigms indeed require fundamentally different abilities, confirming the previous findings suggesting that acoustical listening expertise is not a single skill but consists of several abilities (Kuusinen and Lokki, 2020). however, expertise in the perceptual assessment of room acoustic conditions can only be achieved by familiarization and specific training of all participants prior to the listening test, whereas self-reports and socio-demographic information represent rather unreliable indicators.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, in a study by Kreimann et al (1990), clinical experts used different, individual strategies to identify dysphonia (a larynx malfunction that causes hoarse voice) in the vocal recordings compared to a sample of naive listeners who rather consistently relied on the voices' fundamental frequency. Also, a study by Kuusinen and Lokki (2020) observed that listening test participants benefited from acoustic expertise and experience in a discrimination task in which different room impulse responses were presented with the same source signal but not if the source signal also changed between the different stimuli.…”
Section: A Knowledge Experience and Perceptionmentioning
confidence: 99%
See 1 more Smart Citation